p53 alterations in sequential biopsies of Asian follicular lymphoma: a study of immunohistochemical staining pattern and gene mutations by PCR-SSCP in paraffin-embedded tissues - Shaminie, J.; Peh, S.C.; Tan, J. (2005)
Aim: Tumour suppressor gene p53 is a common target in carcinogenesis, reported to be altered and functionally inactive in 70 of human cancers. Although p53 mutations are less commonly present in haematological malignancies when compared with other solid tumours, they have been reported in histological transformation of follicular lymphoma. We aimed to investigate the frequency of p53 gene alterations in paraffin-embedded tissue using commercially available PCR-SSCP, and to correlate the results with P53 protein expression by immunohistochemistry. Methods: Surgical samples from seven patients with a total of 17 sequential biopsies were retrieved for the study of p53 gene expression using immunohistochemical stain, and gene status by PCR-SSCP for exons 5-8. The tumours were graded according to the WHO classification criteria. P53 was distinctly over-expressed in five transformed higher grade biopsies, and all except one showed electrophoretic mobility shift in PCR-SSCP analysis. Sequencing analysis revealed single nucleotide substitutions in three of four of these high-grade transformed cases with band shift (75), whereas some other studies reported a lower frequency of 25-30, and mobility shift result was found to correlate with P53 expression. Lower grade tumours without P53 over-expression did not demonstrate band shift, and sequencing analysis did not reveal mutations. Conclusions: We demonstrated the feasibility of adopting PCR-SSCP for screening of p53 mutations in archival tissue samples in this study, and there is a strong correlation of p53 gene over-expression and mutation events in high-grade transformed turnours.